1994
DOI: 10.1016/0735-1097(94)90127-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronically decreased aortic distensibility causes deterioration of coronary perfusion during increased left ventricular contraction

Abstract: These results demonstrate that during increased ventricular contraction, chronically decreased aortic distensibility contributes to a further decrease in the coronary flow reserve ratio, impairs endocardial blood flow and may induce subendocardial ischemia even in the absence of coronary artery stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
94
0
10

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(107 citation statements)
references
References 24 publications
3
94
0
10
Order By: Relevance
“…Another interpretation is that abnormalities in the microcirculation and, therefore, in peripheral vascular resistance, lead to the perturbations in aortic stiffness (41). The hypothesis that coronary flow may be influenced by aortic elastic properties was introduced by Bouvrain et al (42), and was confirmed by experimental studies (37,38). In previous studies, significant correlations between CFR and aortic stiffness assessed by pulse wave velocity have been demonstrated in patients with hypertension and coronary artery disease (43,44).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Another interpretation is that abnormalities in the microcirculation and, therefore, in peripheral vascular resistance, lead to the perturbations in aortic stiffness (41). The hypothesis that coronary flow may be influenced by aortic elastic properties was introduced by Bouvrain et al (42), and was confirmed by experimental studies (37,38). In previous studies, significant correlations between CFR and aortic stiffness assessed by pulse wave velocity have been demonstrated in patients with hypertension and coronary artery disease (43,44).…”
Section: Discussionmentioning
confidence: 82%
“…Several components of the MetS, including high blood pressure, hyperglycemia, and abdominal fat, have been related to increased aortic stiffness (12,15). Relations between microvascular function and aortic stiffness have been reported (37,38). In the Framingham Heart Study offspring cohort increased aortic stiffness was associated with higher forearm vascular resistance at baseline and during reactive hyperemia, and with blunted flow reserve during hyperemia (39).…”
Section: Discussionmentioning
confidence: 99%
“…15 -17 But increased aortic stiffness decreases coronary flow reserve and during increased myocardial contractility endocardial flow becomes impaired with subendocardial ischemia. 16 These undesirable alterations are enhanced with a high-grade coronary stenosis or during reductions in diastolic BP. 18 In stable angina patients there is an inverse relationship between central aortic stiffness and coronary flow.…”
Section: Clinical Cardiology Doi:101002/clcmentioning
confidence: 99%
“…22 Thus, arterial stiffness causes a mismatch between myocardial oxygen demands and myocardial perfusion resulting in subendocardial ischemia, LV diastolic dysfunction and elevation of diastolic filling pressure, which further decreases myocardial perfusion. 22 Indeed, experimental studies have shown that arterial stiffness contributed to a decrease in CFR 26 and has an effect on subendocardial ischemia. 27 Furthermore, Kingwell et al 28 demonstrated that aortic stiffness is an important independent determinant of myocardial ischemic threshold in patients with CAD.…”
Section: Discussionmentioning
confidence: 99%